Voltage Stability Assessments and Their Improvement Using Optimal Placed Static Synchronous Compensator (STATCOM). (23rd August 2022) - Wondie, Tebeje Tesfaw; Tella, Teshome Goa
Abstract : In this paper, static voltage stability assessments and their improvement using analytical and optimization techniques with different loading scenarios are described. In this study, the 400 kV, 230 kV, and 132 kV Ethiopian electric power networks are modeled using Power System Analysis Toolbox (PSAT), and the load flow analysis is carried out using MATLAB source code. Then, different voltage stability indices, such as the user-defined advanced voltage stability index (AVSI), modified voltage stability index (MVSI), and fast voltage stability index (FVSI), are used to identify the voltage unstable buses. Besides this, particle swarm optimization (PSO) is also used to find the optimal size and placement of the Static Synchronous Compensator (STATCOM) for the most severe buses identified by voltage stability indices. The result presents three special arguments: whether the most severe buses that are ranked at the top based on the voltage stability indices are optimal buses for compensation placement or not, the voltage stability improvement, and power loss reduction with the introduction of STATCOM. Accordingly, it is observed that the weakest bus that is identified through the stability indices may not be the optimal placement of the compensation device. It is also indicated that, with the introduction of STATCOM to the optimal selected bus, the network power loss is reduced from 46.65 MW to 33.32 MW and its voltage magnitude in all buses is also improved. All bus voltages are within the IEEE standard acceptable limit.